Moderatisme Islam Dalam Konteks Keindonesiaan - iffaty Zamimah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2018)
This study proves that Islamic moderation has long been known in the Islamic tradition. This at once denied the assumption that Islam is a religious that teaching violence. This research is proved by the verses of the Qur'an that have explained the principle of moderate (washatiyah). Through these verses of the Qur'an, Quraish Shihab interprets Islamic moderatism can be applied to the Indonesian context. This study is carried out by exploring the interpretations made by M. Quraish Shihab through Tafsir Al-Mishbah, Wawasan Al-Qur’an, Membumikan Al-Qur’an and others.